2010
DOI: 10.1007/s10681-010-0159-2
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of rice SSR markers to bamboo

Abstract: Simple sequence repeat (SSR) markers are widely applied in studies of plant molecular genetics due to their abundance in the genome, codominant nature, high repeatability, and transferability in cross-species applications. To investigate the possibility of applying rice SSR markers in bamboo, we selected 120 rice SSR markers that are evenly distributed on rice chromosomes and assessed these for their transferability to 21 different bamboo species. A total of 4847 bands of 2196 alleles were obtained from 82 SSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
(86 reference statements)
2
7
2
Order By: Relevance
“…Most of these fragments were amplified higher than the size of the donor fragment, which is in agreement with the previous study implying that the amplified fragments from the selected species have different allele sizes than those of the donor species [26,24,27].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Most of these fragments were amplified higher than the size of the donor fragment, which is in agreement with the previous study implying that the amplified fragments from the selected species have different allele sizes than those of the donor species [26,24,27].…”
Section: Resultssupporting
confidence: 92%
“…Markers such as Xiabtp424, Xise0443 and Xisep0648 did not score any amplification in either of the bamboo species. The transferability rate obtained in this study is higher than the one reported for various grass family species including bamboo using [18,26,27]. However, the rate is slightly lower than the rice SSR transferability to bamboo that was reported to be 68% [26].…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…The stability of the SSR flanking regions was investigated in different organisms; three Phytophthora species (algae) [13]; rice and bamboo [14]; cotton [15]; Brassica rapa and Arabidopsis thaliana [16]; cowpea, mung bean and adzuki bean [17]; Castanea spp. [18]; Carya [19] and wheat [20].…”
Section: Presentation Of the Hypothesismentioning
confidence: 99%